Negative Outcomes of Internet Usage: The Role of Problematic Internet Use, Loneliness and Depression - Alaedein, Jehad (Jordan Journal of Educational Sciences, 2014)
The current study sought to examine the validity of cognitive-behavioral model for problematic Internet use (PIU) (Caplan, 2003; Davis, 2001) in illustrating the relationships between the preference for online social interaction with loneliness, depression and other symptoms of (PIU), and the role of these variables in developing the negative consequences due to Internet use. Participants were undergraduates (n=451) from a private university in Amman-Jordan, and were (73.8%) females and (26.2%) males respectively. Results showed that the cognitive behavioral model was appropriate for the data. It has been shown that the well-being variables predicted levels of preference for online social interaction and interpreted (6%) of the variances in this variable. In addition, the results revealed that variables of problematic Internet use (PIU) interpreted (18.3%) of the variances in the participants' scores on negative consequences related to the Internet use scale, while variables of loneliness and depression contributed to the interpretation of (4%) of these variances